On the design of porous structures with enhanced fatigue life. (October 2017) - Javid, Farhad; Liu, Jia; Rafsanjani, Ahmad; Schaenzer, Megan; Pham, Minh Quan; Backman, David; Yandt, Scott; Innes, Matthew C.; Booth-Morrison, Christopher; Gerendas, Miklos; Scarinci, Thomas; Shanian, Ali; et al.
Abstract: Many components of gas turbines, including the combustion liners, ducts, casings and sealing structures, comprise metallic sheets perforated with arrays of circular cooling holes. These parts are highly prone to fatigue failure due to the stresses induced by temperature variations during operation. Here, we demonstrate both experimentally and numerically that the fatigue life of these porous components can be greatly enhanced by carefully designing the pores' shape. In particular, we show that while the fatigue life of a metallic sheet with a square array of conventional circular cooling holes is < 100 k cycles, by replacing the pores with novel orthogonal S-shaped holes the life of the structure increases up to more than one million cycles. This is because the S-shaped pores introduce a soft mode of deformation based on rotation of the domains between neighboring holes that significantly affect the stress distribution and crack propagation in the structure.